Removal of Copper and Zinc Metal Ions from Industrial Effluents in Continuous Mode using Modified Date Pits - Mohsen, Huda A.; Ghanim, Alaa N. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Adsorbents based on agricultural biomass have been subjected to several investigations in recent years owing to their low cost and promising adsorption capabilities. This paper aimed to demonstrate the efficiency of utilizing date pits modified with hydrogen peroxide as agricultural biomass in extracting heavy metals from polluted water in a column continuous flow system. The resulting modified adsorbent (MDP) has a surface area of 278.18 m2/g.  The derived adsorbent was investigated under changed operating parameters including the flow rate (4-12) ml/min, pH (4-10), initial metal ion concentration (30-60) mg/L, and temperature (20-50) °C to determine their effect on heavy metals adsorption efficiency. The response surface methodology (RSM) experimental design was utilized to study the primary and combined influence of four key parameters, including (A) initial metal ion concentration, (B) pH solution, (C) solution temperature, and (D) flow rates of the influent, on the metal removing efficiency (Re%). optimization in fact, an analysis of variance (ANOVA) revealed a high coefficient of regression, or R2 > 0.90. Furthermore, the removal efficiency was positively influenced by reducing the initial ion concentration, flow rate, and temperature. in addition, the pH shows maximum effectiveness at a neutral state. In general, Cu (II) adsorption shows a higher affinity to adsorb over the MDP surface compared to Zn (II). The MDP adsorbents exhibited a promising removal efficiency for metal ions and further investigations are needed.